Sarkopenia pada Pasien Sirosis Hepatis: Analisis - Pauliana; Vionita Simanjuntak; Jessica Andrean (PT Kalbe Farma Tbk., 2025)
Sarcopenia is a condition characterized by a decrease in muscle mass, strength, and function. Hepatic cirrhosis is a catabolic condition, the breakdown of muscle protein exceeds its synthesis; it is closely related to the occurrence of sarcopenia. This association is associated with more severe complications of cirrhosis, more frequent hospital visits, and early death. This literature review will provide insight into the importance of appropriate prevention, monitoring, and management of cirrhosis.